2006
DOI: 10.1158/1078-0432.ccr-06-0736
|View full text |Cite
|
Sign up to set email alerts
|

GROα Is Highly Expressed in Adenocarcinoma of the Colon and Down-Regulates Fibulin-1

Abstract: Purpose: The growth-related oncogene a (GROa) is a secreted interleukin-like molecule that interacts with the CXCR2 G-protein^coupled receptor. We found that the mRNA and protein products of GROa are more highly expressed in neoplastic than normal colon epithelium, and we studied potential mechanisms by which GROa may contribute to tumor initiation or growth. Experimental Design: Cell lines that constitutively overexpress GROa were tested for growth rate, focus formation, and tumor formation in a xenograft mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 52 publications
(60 reference statements)
3
48
1
Order By: Relevance
“…The data are consistent with that reported in a previous study, in which the mRNA expression of GROα was found to be significantly increased in colon adenocarcinoma tissue when compared with that in adjacent normal tissue [27]. We further investigated the expression of GROα protein levels in TMAs prepared from LSCC specimens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data are consistent with that reported in a previous study, in which the mRNA expression of GROα was found to be significantly increased in colon adenocarcinoma tissue when compared with that in adjacent normal tissue [27]. We further investigated the expression of GROα protein levels in TMAs prepared from LSCC specimens.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have since implicated a relationship between the expression of GROα and various human cancers [10,[15][16][17][18]. Recently, it has been reported that GROα plays a critical role in human cancers through several potential signaling pathways, including NF-κB [26], phosphatidylinositol-3-kinase [19] and MEKK1/p38 [27]. CXCR2, the receptor of GROα, interacts with this chemokine with high affinity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GRO‐α is a potential mediator of cancer invasion in several human cancers such as gastric cancer26 and colon adenocarcinoma 27. IL‐8 is capable of promoting cancer progression by regulating angiogenesis through autocrine and paracrine mechanisms 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these previously have been reported to be increased in gut inflammation and or colon tumors. [13][14][15][16][17] They also have been reported to be involved in angiogenesis 27 and metastasis. 28,29 Notably, Table 1.…”
Section: Org)mentioning
confidence: 99%
“…10.001. gut and have been reported to show altered expression in colon tumor tissue. [13][14][15][16][17] Inflammation is widely recognized as a component of cancer, with inflammatory bowel diseases known to lead to increased risk of colon carcinogenesis. 18,19 Hence, gastrointestinal inflammatory signaling pathways and their regulation present key targets for prevention and therapeutic intervention.…”
mentioning
confidence: 99%